Field notes contributed by Ann Johnson, December 2, 1996 - Johnson, Annet al (1996)
List of birds and locations contributed by Ann Johnson. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1996. Epson - sheet feed